Tuning synthesis temperature spectrum to unlock multifunctional potential in multi-walled carbon nanotubes for EMI shielding and optical applications - Kamil Kayode, Katibi; Azis, Rabaah Syahidah; Garba Shitu, Ibrahim; Ismail, Ismayadi; Soo Kien, Chen; Kean Pah, Lim; Awang Kechik, Mohd Mustafa; Md Yunos, Khairul Faezah; Abdulhameed Amusa, Abiodun (Korean Society of Industrial Engineering Chemistry, 2025)
Multi-walled carbon nanotubes (MWCNTs) have garnered significant attention for their promising potential in electromagnetic interference (EMI) shielding due to their superior electrical conductivity, structural stability, and multifunctional properties. This study explores how chemical vapor deposition (CVD) synthesis temperatures (700 ◦ C, and 900 ◦ C) affect the structural, morphological, thermal, absorption, optical properties, and EMI shielding of MWCNTs. Using advanced characterization techniques, including High-Resolution Transmission Electron Microscopy (HRTEM), Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Raman spectroscopy, Thermogravimetric Analysis (TGA), and optical absorption spectroscopy, the MWCNTs were thoroughly analyzed. The 900 ◦ C sample exhibited superior EMI shielding effectiveness (38 dB in the X-band) and high optical transmittance of 85 % at 550 nm. In comparison, the 700 ◦ C sample had higher defect density, resulting in lower transmittance (35 %) and reduced shielding (22 dB). These findings demonstrate a direct correlation between higher synthesis temperatures, improved crystallinity, and enhanced electromagnetic and optical performance. This research highlights the potential of MWCNTs for high-performance EMI shielding materials, particularly suited for advanced applications in telecommunications, electronics, and aerospace.